Association of arch height with ankle muscle strength and physical performance in adult men - Zhao, X; Tsujimoto, T; Kim, B; Tanaka, K (Biology of Sport, 2017)
Differences in arch height may have a certain impact on lower extremity muscle strength and physical performance. However, there is little evidence from investigation of the possible correlation of arch height with ankle muscle strength and physical performance measures. Sixty-seven participants took part in this study. Arch height index (AHI) was assessed and categorized using a 3-dimension foot scanner. Ankle muscle strength was measured employing a dynamometer. Physical performance measures including agility, force and proprioception were randomly tested. Compared to the medium AHI, the high AHI had lower plantarflexion and inversion peak torque. The high AHI also had lower peak torque per body weight value for plantarflexion and inversion at 120°/s (P = 0.026 and 0.006, respectively), and dorsiflexion at 30°/s (P = 0.042). No significant ankle muscle strength difference was observed between the low and medium AHI. Additionally, AHI was negatively correlated with eversion and inversion peak torque at 120°/s, and negatively associated with plantarflexion, eversion and inversion peak torque per body weight at both 30°/s and 120°/s (r ranged from -0.26 to -0.36, P values < 0.050). However, no significant relationship was found between arch height and physical performance measures. The results showed that high arches had lower ankle muscle strength while low arches exhibited greater ankle muscle strength. Arch height was negatively associated with ankle muscle strength but not related to physical performance. We suggest that the lower arch with greater ankle muscle strength may be an adaptation to weight support and shock absorption.